Analisis Pengaruh Relationship Marketing Dan Kualitas Layanan Terhadap Kepuasan Dan Loyalitas Nasabah Pada PT. Pegadaian (Persero) Cabang Manado Utara - Rangan, Febry Venesia Luciana (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The purpose of this research is to find out and analyze the effect of Relationship Marketing and Service Quality on Customer Satisfaction and Customer Loyalty at PT. Pegadaian (Persero) North Manado Branch. Research findings show that Relationship Marketing has a significant effect on customer satisfaction, while service quality has insignificant effect on customer satisfaction. Relationship marketing has a significant effect on customer loyalty, service quality also has a significant effect on customer loyalty, while customer satisfaction has insignificant effect on customer loyalty. Based on the findings it is suggested the Relationship Marketing to have significant effect on both customer satisfaction and loyalty in Kredit Cepat Aman (KCA). This means that the management of Pegadaian should pay more attention on this matter. In this case in order to create more loyal customers the solution is to emphasize on Relationship Marketing. Keywords: Relationship Marketing, Service Quality, Customer Satisfaction, Customer Loyalty